2018
DOI: 10.3390/met8080582
|View full text |Cite
|
Sign up to set email alerts
|

PCBN Performance in High Speed Finishing Turning of Inconel 718

Abstract: Inconel 718 is a Ni superalloy widely used in high responsibility components requiring excellent mechanical properties at high temperature and elevated corrosion resistance. Inconel 718 is a difficult to cut material due to the elevated temperature generated during cutting, its low thermal conductivity, and the strong abrasive tool wear during cutting process. Finishing operations should ensure surface integrity of the component commonly requiring the use of hard metal tools with sharp tool edges and moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…The progression of tool wear resulted in an increased effective tool tip radius that was related to the decrease in R a values. Similarly, the authors have observed this phenomenon in processes of finishing turning of Inconel 718 [36].…”
Section: Surface Qualitymentioning
confidence: 53%
“…The progression of tool wear resulted in an increased effective tool tip radius that was related to the decrease in R a values. Similarly, the authors have observed this phenomenon in processes of finishing turning of Inconel 718 [36].…”
Section: Surface Qualitymentioning
confidence: 53%
“…However, for higher cutting speeds, the chipping was dominant, as the beginning caused the original honing of the cutting edge, which was not so defined. The authors obtained similar results during the finishing turning of Inconel 718 [32].…”
Section: Analysis Of Surface Qualitymentioning
confidence: 53%
“…The machining of "difficult to cut materials" such as the nickel-based superalloys used in turbine blades requires an extended tool life for unhindered machining [35]. Traditional carbide tools are limited to working in the range of 30 m/min to 70 m/min because of their poor thermochemical stability; however, they can be used at high feeds due to their high toughness.…”
Section: Advanced Machining Techniquesmentioning
confidence: 99%